ANALYSIS OF PRODUCT QUALITY AND PRICE AFFECT DEMAND FOR A PRODUCT - Zakaria, Roza Hazli; Sepik, Losen (DIVERSITY Logic Journal Multidisciplinary, 2025)
Background. One of the key components of a marketing plan is price. Competitive prices can increase product attractiveness in the eyes of consumers, especially in price-sensitive market segments. The enthusiasts who are prospective buyers want the product to be of high quality, particularly in terms of fulfilling customer expectations so that they become satisfied and loyal to the company. Research Purpose. Analyzing product quality and price affect demand for a product. Research Method. This study is quantitative in nature and uses saturation sampling approaches to collect primary data from 50 consumers who were given questionnaires. Questionnaires and literature reviews were used as the data gathering approach. While conventional assumption tests include testing for normalcy, heteroscedasticity, and multicollinearity, instrument tests include tests for validity and reliability. Multiple linear regression was used to analyze the data. Findings. The results showed that the price variable had a significant effect on product demand (tcount = 0.025), while the product quality variable had a significant effect on product demand (tcount = 0.000). Conclusion. To become more competitive in the market, every business should constantly enhance the quality of its products and take customer preferences into account while adjusting prices.